Predictive Analysis Between Topographic, Pachymetric and Wavefront Parameters in Keratoconus, Suspects and Normal Eyes: Creating Unified Equations to Evaluate Keratoconus. (3rd March 2016) - Prakash, Gaurav; Suhail, Muhammad; Srivastava, Dhruv
ABSTRACT: Purpos e: To perform prediction analysis between topographic, pachymetric and wavefront parameters in keratoconus, suspects, and normal cases and to look at the possibility of a unified equation to evaluate keratoconus. Methods : This cross-sectional, observational study was done in cornea services of a specialty hospital. Fifty eyes of 50 candidates with a diagnosis of normal, keratoconus suspect, and keratoconus were included in each group (total 150 eyes). All eyes underwent detailed analysis on Scheimplug + Placido device (Sirius, CSO, Italy). Main parameters evaluated were topographic [maximum keratometry (Max K m ), average keratometry and astigmatism at 3, 5, and 7 mm], pachymetric [central and minimum corneal thickness (MCT) and their difference, corneal volume] and corneal aberrations [higher order aberrations root-mean-square (HOARMS), coma, spherical, residual].Central tendency, predictive fits and regression models, were computed. Results : The measured variables had a significant difference in mean between the three groups (Kruskal–Wallis, p < 0.001). Max K m, MCT, and HOARMS had significant fits with other topographic, pachymetric and wavefront parameters, respectively. Inter-relations between these three (Max K m, MCT, and HOARMS) were also stronger for keratoconus ( R 2 from 0.75 to 0.33) compared to suspect/normal eyes ( R 2 from 0.15 to 0.003). These three variables (Max K m, MCT and HOARMS) were used as representative variables to create the unified equations. The equation for the pooled data was ( K max = 59.5 + 2.3 × HOARMS−0.03 × MCT; R 2 = 0.7, p < 0.001). Conclusions : Major variables used for grading keratoconus (MaxKm, MCT, HOARMS) can be linked by linear regression equations to predict the pathology's behavior.